Global Shape Information Increases but Color Information Decreases the Composite Face Effect. (May 2015) - Retter, Talia L; Rossion, Bruno
The separation of visual shape and surface information may be useful for understanding holistic face perception—that is, the perception of a face as a single unit (Jiang, Blanz, & Rossion, 2011, Visual Cognition, 19, 1003–1034). A widely used measure of holistic face perception is the composite face effect (CFE), in which identical top face halves appear different when aligned with bottom face halves from different identities. In the present study the influences of global face shape (ie contour of the face) and color information on the CFE are investigated, with the hypothesis that global face shape supports but color impairs holistic face perception as measured in this paradigm. In experiment 1 the CFE is significantly increased when face stimuli possess natural global shape information than when cropped to a generic (ie oval) global shape; this effect is not found when the stimuli are presented inverted. In experiment 2 the CFE is significantly decreased when face stimuli are presented with color information than when presented in grayscale. These findings indicate that grayscale stimuli maintaining natural global face shape information provide the most adept measure of holistic face perception in the behavioral composite face paradigm. More generally, they show that reducing different types of information diagnostic for individual face perception can have opposite effects on the CFE, illustrating the functional dissociation between shape and surface information in face perception.